La contemporaneidad, época y categoría histórica - Julio Aróstegui Sánchez (Mélanges de la Casa de Velázquez, 2006)
Contemporariness is a concept that began to circulate with the liberal revolutions of the 18th and 19th centuries. The definition of what was contemporary came into being in intellectual, political, historiographic and literary circles as a new category of historical time referring, at a time when the liberal mentality was forming, to «coetaneous history» or «lived history». With the passage of time, the meaning of contemporariness shifted from its original position as a category of time to denote a historical age – indeed the very one that was ushered in by the great revolutions. Contemporary History was built up in the course of the 20th century; however. this Contemporary History which is a prolongation of Modern History would no longer be coetaneous history but the history ushered in by revolution, which is a category unto itself. The new movement towards a history of coetanous time is now called history of the present.